Different starch sources affect physical characteristics of extruded feeds prepared for the Malaysian mahseer, Tor tambroides - Ishak, Sairatul Dahlianis; Yusof, Yus Aniza; Kamarudin, Mohd Salleh (Taylor and Francis, 2020)
Starches from three local crops (sago, Metroxylon sagu; cassava, Manihot esculenta; and taro, Colocasia esculenta) were tested as replacements for corn starch in the production of extruded feed for the Malaysian mahseer, Tor tambroides . Four test feeds were formulated to contain 40.00% protein and 23.44% starch, and extruded using a single-screw extruder (120 rpm speed, 2 mm diameter die head). Temperatures at the feeding, mixing, compressing, and die zones were set at 60°C, 100°C, 120°C, and 160°C, respectively. Physical properties used to evaluate the quality of the extrudates were expansion ratio, bulk density, true density, pellet durability index, water stability, floatability index, sinking velocity, and sample microstructure. Results showed that test starches produced extrudates with fairly equal quality to corn starch extrudates for expansion ratio, pellet durability index, pellet durability index, and floatability index. Cassava starch extrudates had the best external appearance observed under electron microscopy. This study shows the potential that these three starches have in aquafeed production especially in producing quality Malaysian mahseer feed.